KAPITALISME PENDIDIKAN DI ERA MODERN: Antara Idealita dan Realita - Qodriah, Lailatul; Aisy, Jihaan Rihhadatul; Ramadhani, Nidhya Risthy; Muzaki, Muhammad; Khobir, Abdul (Department of Islamic Education Management, 2025)
Educational capitalism in the modern era refers to the process of commodification of education that increasingly dominates the global education system. On the one hand, this capitalism creates economic opportunities, increases access to higher education, and encourages innovation. However, on the other hand, this phenomenon often conflicts with the ideal values ​​of education, which should be oriented towards equal opportunities, character development, and the formation of moral humans. In this context, education, which was originally expected to be a means to form intelligent and characterful individuals, has now often become a commercial product that is traded for profit. Educational institutions, both state and private, increasingly prioritize financial gain over the deeper goals of education itself. This has implications for the gap in access to education, where groups of people with low economic status are increasingly marginalized, while quality education can only be reached by the upper economic class. Using the literature study method and descriptive approach, this article will discuss the definition of educational capitalism, the positive and negative impacts of capitalism on education, and the ideals and realities of educational capitalism.